Synthesis method of indium-tin-based nano composite material
Through the supercritical fluid-assisted synthesis method, supercritical carbon dioxide is used for reaction, which solves the inefficiency and unenvironmental problems of the existing indium tin-based nanocomposite synthesis methods, and achieves efficient and environmentally friendly nanomaterial synthesis, improving material performance and product purity.
Patent Information
- Application Number
- CN202411807084.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
The existing indium tin-based nanocomposite synthesis methods have problems such as inefficiency and unenvironmental protection, and it is difficult to ensure the performance of nanomaterials and the purity and uniformity of products.
The supercritical fluid-assisted synthesis method is adopted to dissolve indium nitrate and stannous chloride in deionized water, mix and add active agent and alkali liquid to adjust the pH value to form indium tin hydroxide precipitation, and react with supercritical carbon dioxide in an autoclave to control the temperature and pressure to ensure the control of the morphology and size of the nanoparticles.
The efficient and environmentally friendly synthesis of indium tin-based nanocomposites is achieved, the performance of nanomaterials and the purity and uniformity of products are improved, and the problems of using harmful solvents and high temperature and high pressure conditions in traditional methods are solved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mineral processing, and in particular to a method for synthesizing an indium tin-based nanocomposite material. Background Art
[0002] In recent years, indium tin-based nanocomposites have attracted much attention due to their wide applications in transparent conductive films, sensors, optoelectronic devices, and other fields. Traditional synthesis methods mainly include sol-gel method, chemical vapor deposition method, and hydrothermal method. These methods can control the morphology and size of nanomaterials to a certain extent. In addition, chemical reduction method is also a commonly used synthesis method. It can react at a lower temperature and has good operability. However, the reducing agents and solvents used in traditional chemical reduction methods are often not environmentally friendly, and the purity and uniformity of the reaction products are difficult to guarantee.
[0003] However, the traditional synthesis method has met the preparation needs of indium tin-based nanocomposites to a certain extent, but there are still many shortcomings. First, it usually requires higher temperatures and complex process conditions, and may have an adverse effect on the performance of nanomaterials. Secondly, the reducing agents and solvents used in traditional chemical reduction methods pollute the environment and do not meet the requirements of green chemistry. In addition, these methods have certain limitations in controlling the morphology and size of nanomaterials, resulting in poor consistency and repeatability of the products, which is difficult to meet the needs of high-performance applications.
[0004] Therefore, there is a need for an efficient and environmentally friendly method for synthesizing indium tin-based nanocomposites. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for synthesizing an indium tin-based nanocomposite material, aiming to solve the problems of low efficiency and environmental pollution of the existing indium tin-based nanocomposite material synthesis methods.
[0006] To achieve the above object, the present invention provides a method for synthesizing an indium tin-based nanocomposite material, the method comprising the following steps:
[0007] Dissolving indium nitrate and stannous chloride in deionized water respectively to prepare precursor solutions of indium salt and tin salt;
[0008] Mixing precursor solutions of indium salt and tin salt in a certain proportion to obtain a metal ion mixed solution;
[0009] Under stirring conditions, adding an active agent to the metal ion mixed solution for stirring, and adding an alkali solution dropwise until the pH value of the solution is adjusted to 8 to 9, thereby obtaining an indium tin hydroxide precipitate;
[0010] Transfer the indium tin hydroxide precipitate to a high-pressure reactor, and add an appropriate amount of ethanol or ethanol-water mixed solvent to ensure that the precipitate can be fully dispersed;
[0011] Inject high-purity carbon dioxide into the high-pressure reactor, increase the pressure to above the critical pressure, increase the temperature to above the critical temperature, and maintain the set temperature and pressure for 2 to 4 hours;
[0012] The reaction product suspension is taken out and filtered to obtain an indium tin-based nanocomposite material.
[0013] Furthermore, the synthesis method of the indium tin-based nanocomposite material further comprises the following steps:
[0014] The indium tin-based nanocomposite material is washed with ethanol to remove residual organic matter and impurities;
[0015] The washed nanocomposite material is placed in a vacuum drying oven at 60-80° C. to be dried to obtain a dry nanopowder;
[0016] The nano powder is transferred to a sintering furnace and sintered at 300° C. to 500° C. in an inert atmosphere for 2 to 4 hours.
[0017] Furthermore, the step of mixing the precursor solutions of indium salt and tin salt in a certain proportion to obtain a mixed solution of metal ions further includes:
[0018] Add ascorbic acid to the precursor solution of tin salt to obtain a stable Sn 2+ Saline solution;
[0019] Sodium citrate and polyvinyl pyrrolidone were added to the metal ion mixed solution to ensure the dispersion of nanoparticles.
[0020] Furthermore, the step of adding an active agent to the metal ion mixed solution under stirring, stirring, and adding an alkali solution dropwise until the pH value of the solution is adjusted to 8 to 9 to obtain an indium tin hydroxide precipitate also includes:
[0021] The obtained indium tin hydroxide precipitate is washed multiple times with deionized water to remove impurities and unreacted ions in the solution.
[0022] Furthermore, the step of injecting high-purity carbon dioxide into the high-pressure reactor, increasing the pressure to above the critical pressure, increasing the temperature to above the critical temperature, and maintaining the set temperature and pressure for 2 to 4 hours also includes:
[0023] Adding a reducing agent under supercritical conditions ensures the reduction of the nanoparticles;
[0024] After the reaction is completed, the temperature and pressure of the reactor are gradually reduced to return the carbon dioxide from the supercritical state to the gaseous state, and the gaseous carbon dioxide is released into the collection device.
[0025] Furthermore, the step of injecting high-purity carbon dioxide into the high-pressure reactor, increasing the pressure to above the critical pressure, increasing the temperature to above the critical temperature, and maintaining the set temperature and pressure for 2 to 4 hours also includes:
[0026] A co-solvent is added to supercritical carbon dioxide to form a supercritical carbon dioxide-co-solvent mixed medium to improve the solubility of an indium tin-based metal precursor.
[0027] Furthermore, the co-solvent includes at least one of ethanol, methanol and water.
[0028] The present invention provides a method of preparing indium tin-based nanocomposite materials by using supercritical fluid-assisted synthesis and adding auxiliary reagents. Supercritical fluid-assisted synthesis reduces the use of organic solvents, and supercritical fluids have excellent mass transfer and heat transfer properties, making it easy to control the size and distribution of nanoparticles. At the same time, the preparation process is simple, the introduction of impurities is reduced, and the purity of the material is improved. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.
[0031] In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0032] Supercritical fluid (SCF) is a special state of matter between gas and liquid, existing above the critical temperature and critical pressure. Supercritical fluid has unique physical and chemical properties, such as high density, high diffusion coefficient, low viscosity and zero surface tension, making it an ideal reaction medium for the synthesis of nanomaterials. The use of supercritical fluid to assist in the synthesis of indium tin-based nanocomposites can achieve precise control of the size, morphology and composition of nanoparticles, while also having the advantages of being green and environmentally friendly and having high product purity.
[0033] The present invention also discloses specific application examples 1-3 and flotation reagent formulas and performance comparison experiments of control examples 1-2 using the prior art, which are as follows:
[0034] Embodiment 1:
[0035] raw material:
[0036] 1. Indium salt: indium nitrate (In(NO3)3·xH2O), tin salt: stannous chloride (SnCl2·2H2O)
[0037] 2. Surfactant: Polyvinylpyrrolidone (PVP, molecular weight 40000)
[0038] 3. Precipitant: Ammonia
[0039] 4. Solvent: deionized water, anhydrous ethanol
[0040] 5. Supercritical medium: carbon dioxide
[0041] Preparation steps:
[0042] S1. Dissolve 90 mmol of indium nitrate and 10 mmol of stannous chloride in 100 mL of deionized water to obtain a metal ion mixed solution;
[0043] S2, adding PVP to the metal ion mixed solution, the ratio of the mass of PVP to the total mass of metal ions being 1:1, and stirring until dissolved;
[0044] S3, under stirring conditions, adding 1 mol / L ammonia solution dropwise, adjusting the pH to 8.5, and generating indium tin hydroxide precipitation;
[0045] S4, separating the indium tin hydroxide precipitate by centrifugation, and washing with deionized water to remove impurities in the indium tin hydroxide;
[0046] S5, dispersing the washed indium tin hydroxide in 50 ml of anhydrous ethanol and transferring it into a high-pressure reactor;
[0047] S6. Inject supercritical CO2 into the autoclave, set the temperature to 40°C, the pressure to 12 MPa, and maintain supercritical conditions for 2 hours;
[0048] S7, after the reaction is completed, the pressure and temperature are slowly lowered to take out the reaction product suspension;
[0049] S8, washing the reaction suspension with ethanol and deionized water and drying at 70° C. for 12 hours to obtain an indium tin-based nanocomposite material;
[0050] S9, placing the indium tin-based nanocomposite material in a sintering furnace, and calcining it at 400° C. for 12 hours in an air atmosphere to obtain a dry indium tin-based nanocomposite material powder.
[0051] Embodiment 2:
[0052] raw material:
[0053] 1. Indium salt: indium nitrate (In(NO3)3·xH2O), tin salt: stannous chloride (SnCl2·2H2O)
[0054] 2. Surfactant: PVP
[0055] 3. Reducing agent: ascorbic acid
[0056] 4. Precipitant: Sodium hydroxide
[0057] 5. Solvent: deionized water, anhydrous ethanol
[0058] 6. Supercritical medium: carbon dioxide
[0059] Preparation steps:
[0060] S1. Dissolve 90 mmol of indium nitrate and 10 mmol of stannous chloride in 100 mL of deionized water to obtain a metal ion mixed solution;
[0061] S2, adding 1 mol / L sodium hydroxide solution dropwise to the metal ion mixed solution, adjusting the pH to 8.5, and generating indium tin hydroxide precipitate;
[0062] S3, separating the indium tin hydroxide precipitate by centrifugation, and washing with deionized water to remove impurities in the indium tin hydroxide;
[0063] S4, dispersing the washed indium tin hydroxide in 50 ml of anhydrous ethanol, adding ascorbic acid, wherein the molar ratio of ascorbic acid to metal ions is 2:1, stirring evenly, and transferring to a high-pressure reactor;
[0064] S5, inject supercritical CO2 into the autoclave, set the temperature to 50°C, set the pressure to 15MPa, and maintain supercritical conditions for 3 hours;
[0065] S6. After the reaction is completed, the pressure and temperature are slowly lowered to take out the reaction product suspension;
[0066] S7, washing the reaction suspension with ethanol and deionized water and drying at 70° C. for 12 hours to obtain an indium tin-based nanocomposite material;
[0067] S8. placing the indium tin-based nanocomposite material in a sintering furnace, and calcining it at 400° C. for 12 hours in an air atmosphere to obtain a dry indium tin-based nanocomposite material powder.
[0068] In this embodiment, the green reducing agent ascorbic acid is used to achieve in-situ reduction. It is understandable that one or more of glucose and citric acid can also be used as green reducing agents. The reducing agent slowly releases reducing properties under supercritical conditions, reduces metal ions in-situ, and forms metal or metal oxide nanoparticles. By adjusting the amount of the reducing agent and the reaction time, the desired nanomaterial can be obtained.
[0069] Embodiment 3:
[0070] raw material:
[0071] 1. Indium salt: indium nitrate (In(NO3)3·xH2O), tin salt: stannous chloride (SnCl2·2H2O)
[0072] 2. Surfactant: Polyvinylpyrrolidone (PVP, molecular weight 40000)
[0073] 3. Precipitant: Sodium hydroxide
[0074] 4. Solvent: deionized water, anhydrous ethanol, anhydrous methanol
[0075] 5. Supercritical medium: carbon dioxide
[0076] Preparation steps:
[0077] S1. Dissolve 90 mmol of indium nitrate and 10 mmol of stannous chloride in 100 mL of deionized water to obtain a metal ion mixed solution;
[0078] S2, adding 1 mol / L sodium hydroxide solution dropwise to the metal ion mixed solution, adjusting the pH to 8.5, and generating indium tin hydroxide precipitate;
[0079] S3, separating the indium tin hydroxide precipitate by centrifugation, and washing with deionized water to remove impurities in the indium tin hydroxide;
[0080] S4, dispersing the washed indium tin hydroxide in 50 ml of anhydrous methanol for redispersion, and transferring it into a high-pressure reactor;
[0081] S5. Inject supercritical CO2 into the autoclave, with the volume ratio of CO2 to methanol being 4:1, to form a supercritical CO2-methanol mixed medium, set the temperature to 40°C, set the pressure to 12 MPa, and maintain the supercritical condition for 2 hours;
[0082] S6. After the reaction is completed, the pressure and temperature are slowly lowered to take out the reaction product suspension;
[0083] S7, washing the reaction suspension with ethanol and deionized water and drying at 70° C. for 12 hours to obtain an indium tin-based nanocomposite material;
[0084] S8. placing the indium tin-based nanocomposite material in a sintering furnace, and calcining it at 400° C. for 12 hours in an air atmosphere to obtain a dry indium tin-based nanocomposite material powder.
[0085] In this embodiment, methanol is introduced as a co-solvent to improve the reaction efficiency. Adding a co-solvent to supercritical CO2 can form a supercritical CO2-co-solvent mixed medium, which can improve the solubility of the metal precursor and promote sufficient contact between the reactants. By adjusting the ratio of supercritical CO2 to the co-solvent, the reaction conditions can be optimized, the synthesis time can be shortened, and the uniformity and size distribution of the nanoparticles can be improved to improve the reaction efficiency. It is understandable that the co-solvent can also be ethanol. When a smaller particle size or higher material performance is required, methanol can be used as a co-solvent; when safety, green environmental protection and convenient operation are emphasized, ethanol can be used as a co-solvent.
[0086] Comparative Example 1:
[0087] raw material:
[0088] 1. Indium salt: indium nitrate (In(NO3)3·xH2O), tin salt: stannous chloride (SnCl2·2H2O)
[0089] 2. Surfactant: Polyvinylpyrrolidone (PVP, molecular weight 40000)
[0090] 3. Precipitant: Ammonia
[0091] 4. Solvent: deionized water, anhydrous ethanol
[0092] Preparation steps:
[0093] S1. Dissolve 90 mmol of indium nitrate and 10 mmol of stannous chloride in 100 mL of deionized water to obtain a metal ion mixed solution;
[0094] S2, adding 1 mol / L ammonia solution dropwise to the metal ion mixed solution, adjusting the pH to 8.5, and generating indium tin hydroxide precipitate;
[0095] S3, separating the indium tin hydroxide precipitate by centrifugation, and washing with deionized water to remove impurities in the indium tin hydroxide;
[0096] S4, dispersing the washed indium tin hydroxide in 50 ml of anhydrous ethanol to react;
[0097] S5, washing the suspension obtained from the reactants with ethanol and deionized water and drying at 70° C. for 12 hours to obtain an indium tin-based nanocomposite material;
[0098] S6. placing the indium tin-based nanocomposite material in a sintering furnace, and calcining the material at 400° C. for 12 hours in an air atmosphere to obtain a dry indium tin-based nanocomposite material powder.
[0099] Among them, this comparative example adopts the traditional precipitation method without supercritical CO2 treatment.
[0100] Comparative Example 2:
[0101] raw material:
[0102] 1. Indium salt: indium nitrate (In(NO3)3·xH2O), tin salt: stannous chloride (SnCl2·2H2O)
[0103] 2. Precipitant: Ammonia
[0104] 3. Solvent: deionized water, anhydrous ethanol
[0105] 4. Supercritical medium: carbon dioxide
[0106] Preparation steps:
[0107] S1. Dissolve 90 mmol of indium nitrate and 10 mmol of stannous chloride in 100 mL of deionized water to obtain a metal ion mixed solution;
[0108] S2, adding 1 mol / L ammonia solution dropwise to the metal ion mixed solution, adjusting the pH to 8.5, and generating indium tin hydroxide precipitate;
[0109] S3, separating the indium tin hydroxide precipitate by centrifugation, and washing with deionized water to remove impurities in the indium tin hydroxide;
[0110] S4, dispersing the washed indium tin hydroxide in 50 ml of anhydrous ethanol and transferring it into a high-pressure reactor;
[0111] S5, inject supercritical CO2 into the autoclave, set the temperature to 40°C, set the pressure to 12MPa, and maintain supercritical conditions for 2 hours;
[0112] S6. After the reaction is completed, the pressure and temperature are slowly lowered to take out the reaction product suspension;
[0113] S7, washing the reaction suspension with ethanol and deionized water and drying at 70° C. for 12 hours to obtain an indium tin-based nanocomposite material;
[0114] S8. placing the indium tin-based nanocomposite material in a sintering furnace, and calcining it at 400° C. for 12 hours in an air atmosphere to obtain a dry indium tin-based nanocomposite material powder.
[0115] Among them, this comparative example adopts a supercritical CO2 treatment method without adding auxiliary reagents.
[0116] Performance comparison data:
[0117] Table 1 Performance test of indium tin based nanocomposite materials
[0118]
[0119] Data Analysis:
[0120] Average particle size of nanoparticles: In Example 1, the nanoparticles have the smallest particle size and are uniform in size under the action of PVP. In Example 2 and Example 3, due to the reducing effect of ascorbic acid or the effect of adding a co-solvent, the particle sizes are slightly larger than in Example 1, but larger than in Control Example 1-2. In Control Example 1, the particle size is larger and unevenly distributed due to the lack of the assistance of a supercritical fluid. Although Control Example 2 has undergone supercritical treatment, it lacks the addition of auxiliary agents, and the particle size is also larger than in Examples 1-3.
[0121] Conductivity: Example 2 has the highest conductivity because the in-situ reduction improves the crystallinity and carrier concentration of the material. The conductivity of Example 2 is also significantly higher than that of the control group, indicating that the active agent and co-solvent added in Examples 1 and 3 help to improve the material performance. The conductivity in Control Example 1 is the lowest, indicating that the material prepared by the conventional method has poor performance. Although the conductivity of Control Example 2 uses a supercritical fluid, it is still lower than that of the examples, indicating the importance of adding auxiliary reagents.
[0122] Optical transmittance: Example 2 has the highest optical transmittance due to its moderate particle size and good dispersibility. The optical transmittances of Example 1 and Example 3 are also higher than that of the control group, indicating that supercritical fluid assistance and the addition of auxiliary agents can help improve the optical properties of the material. Because the control example 1 uses the traditional preparation method, the particle size is too large, which easily leads to particle agglomeration, thereby increasing light scattering. Therefore, the optical transmittance of the control example 1 is the lowest. The transmittance of the control example 2 is improved compared with the control example 1, but it is still lower than that of Examples 1-3, reflecting the importance of adding auxiliary agents.
[0123] Experimental conclusion:
[0124] Through the experimental data of the above three groups of embodiments and two groups of control embodiments, it can be seen that the performance of the indium tin-based nanocomposite material is significantly improved by supercritical fluid and the addition of auxiliary reagents in the present invention, especially in terms of particle size control, electrical conductivity and optical transmittance, which are superior to the prior art.
[0125] In combination with all the above embodiments, the present invention prepares indium tin-based nanocomposites by using supercritical fluid-assisted synthesis and adding auxiliary reagents, thereby achieving precise control of the size, morphology and composition of nanoparticles. At the same time, by adding auxiliary reagents, the original reduction of metal ions can be achieved, the material properties of the nanocomposites can be improved, the material purity can be improved, and the advantages of green environmental protection and high product purity can be achieved, thereby solving the problems of low efficiency and environmental pollution of the existing synthesis methods of indium tin-based nanocomposites.
[0126] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for synthesizing an indium tin-based nanocomposite material, characterized in that: The following steps are involved: Dissolving indium nitrate and stannous chloride in deionized water respectively to prepare precursor solutions of indium salt and tin salt; Mixing precursor solutions of indium salt and tin salt in a certain proportion to obtain a metal ion mixed solution; Under stirring conditions, adding an active agent to the metal ion mixed solution for stirring, and adding an alkali solution dropwise until the pH value of the solution is adjusted to 8 to 9, thereby obtaining an indium tin hydroxide precipitate; Transfer the indium tin hydroxide precipitate to a high-pressure reactor, and add an appropriate amount of ethanol or ethanol-water mixed solvent to ensure that the precipitate can be fully dispersed; Inject high-purity carbon dioxide into the high-pressure reactor, increase the pressure to above the critical pressure, increase the temperature to above the critical temperature, and maintain the set temperature and pressure for 2 to 4 hours; The reaction product suspension is taken out and filtered to obtain an indium tin-based nanocomposite material.
2. The method for synthesizing the indium tin-based nanocomposite material according to claim 1, characterized in that: The synthesis method of the indium tin-based nanocomposite material further comprises the following steps: The indium tin-based nanocomposite material is washed with ethanol to remove residual organic matter and impurities; The washed nanocomposite material is placed in a vacuum drying oven at 60-80° C. to be dried to obtain a dry nanopowder; The nano powder is transferred to a sintering furnace and sintered at 300° C. to 500° C. in an inert atmosphere for 2 to 4 hours.
3. The method for synthesizing the indium tin-based nanocomposite material according to claim 1, characterized in that: The step of mixing the precursor solutions of indium salt and tin salt in a certain proportion to obtain a mixed solution of metal ions also includes: Add ascorbic acid to the precursor solution of tin salt to obtain a stable Sn 2+ Saline solution; Sodium citrate and polyvinyl pyrrolidone were added to the metal ion mixed solution to ensure the dispersion of nanoparticles.
4. The method for synthesizing the indium tin-based nanocomposite material according to claim 1, characterized in that: The step of adding an active agent to the metal ion mixed solution under stirring conditions, stirring, and adding an alkali solution dropwise until the pH value of the solution is adjusted to 8 to 9 to obtain an indium tin hydroxide precipitate also includes: The obtained indium tin hydroxide precipitate is washed multiple times with deionized water to remove impurities and unreacted ions in the solution.
5. The method for synthesizing the indium tin-based nanocomposite material according to claim 1, characterized in that: The step of injecting high-purity carbon dioxide into the high-pressure reactor, increasing the pressure to above the critical pressure, increasing the temperature to above the critical temperature, and maintaining the set temperature and pressure for 2 to 4 hours also includes: Adding a reducing agent under supercritical conditions ensures the reduction of the nanoparticles; After the reaction is completed, the temperature and pressure of the reactor are gradually reduced to return the carbon dioxide from the supercritical state to the gaseous state, and the gaseous carbon dioxide is released into the collection device.
6. The method for synthesizing the indium tin-based nanocomposite material according to claim 1, characterized in that: The step of injecting high-purity carbon dioxide into the high-pressure reactor, increasing the pressure to above the critical pressure, increasing the temperature to above the critical temperature, and maintaining the set temperature and pressure for 2 to 4 hours also includes: A co-solvent is added to supercritical carbon dioxide to form a supercritical carbon dioxide-co-solvent mixed medium to improve the solubility of an indium tin-based metal precursor.
7. The method for synthesizing the indium tin-based nanocomposite material according to claim 6, characterized in that: The co-solvent includes at least one of ethanol, methanol and water.
Citation Information
Patent Citations
Method for preparing microporous ITO (Indium Tin Oxide) fiber by applying supercritical fluid melt-blown spinning
CN103184565A
Method for preparing microporous ITO (indium tin oxide) fibres by applying spinning of three-screw mixing-extruding machine
CN103184585A
Preparation method and application of nano-doped VIB-family metal oxide particles or dispersoid thereof
CN104341000A
Preparation method and application of nano metal hydroxide particles or dispersoid
CN114620689A
Method for preparing nano metal oxide by using near-supercritical fluid and production equipment
CN115536057A